2000
DOI: 10.1017/s0952523800171068
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic and GABAergic amacrine cells are direct targets of melatonin: Immunocytochemical study of mt1 melatonin receptor in guinea pig retina

Abstract: Distribution of the mt1 melatonin receptor in the guinea pig retina was immunocytochemically investigated using peptide-specific anti-mt1 receptor antibody. Western blots of the guinea pig retina showed a single band at approximately 37 kilodalton (kD) immunoreactive to the anti-mt1 antibody. The most intense immunoreactivity for the mt1 receptor was detected in the cell bodies of ganglion cells. Their dendrites and axons were also immunolabeled. Subpopulations of amacrine cells, the inner plexiform layer, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
51
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 59 publications
8
51
0
Order By: Relevance
“…1). The distribution of MT1 mRNA that we have observed is consistent with data reported in the literature in other mammalian species (12,13).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1). The distribution of MT1 mRNA that we have observed is consistent with data reported in the literature in other mammalian species (12,13).…”
Section: Discussionsupporting
confidence: 92%
“…Melatonin receptors are expressed by several retinal cell types, including the photoreceptors (12,13), suggesting that melatonin receptors may be involved in the regulation of photoreceptor physiology. Indeed, previous studies have reported that melatonin influences the membrane conductance of dark adapted frog photoreceptors (14), acts directly on the rod photoreceptors to increase dark adaptation (15), and potentiates rod signals to ON type bipolar cells in fish retina (16).…”
mentioning
confidence: 99%
“…These cells are also susceptible to the regulatory action of an important circadian modulatory hormone, melatonin [24,31] . Dopaminergic and GABAergic output of the amacrine cells is directly regulated by melatonin [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic and GABAergic output of the amacrine cells is directly regulated by melatonin [31] . Since orexin-A-and orexin-B-positive fi bers [9] and OX-R1 expression [16] have been localized in the SCN, orexins may be involved in the retinohypothalamic tract from the amacrine and ganglion cells projecting to the SCN.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, aMT increases GABA content and regulates the circadian rhythm of its receptors in the CNS [13, 14], and dopaminergic and GABAergic cells are target for aMT [39]. DA exerts its striatal effect acting on both D 1 and D 2 receptors mainly located on GABAergic neurons into the striatum.…”
Section: Discussionmentioning
confidence: 99%